The effect of tube length and cold exit diameter on the cold flow temperature of vortex tube using high temperature working gas - Muhammad Fadhli, Suhaimi; Mohd Hazwan, Yusof (IOP Publishing, 2019)
Vortex tube has been using widely in industry for the cooling process. It is working as a refrigerator which split compressed gas into the hot and cold stream without using any electrical or chemical process. In term of application, the effect of geometrical parameters on the cold flow temperature of vortex tube by using high temperature compressed gas is obscure, and effect of certain working gas has yet to be vigorously researched. Thus, the objective of this analysis is to determine the effect of length of the vortex tube, cold exit diameter and different high temperature working gas. There are 3 different tube length, 3 different cold diameter, and 7 different types of gas are used. The models are designed from SolidWork with several parameters. Simflow, which is free software, is selected to analyse the effect on model numerically. From the results, it is clear that the optimum tube length, cold exit diameter, and working gas are L = 175 mm, d = 4 mm and helium, respectively.